Preliminary study of the Arctiinae (Lepidoptera: Erebidae) from Arequipa, Peru - Grados, Juan (2021)
A preliminary list and diagnosis of the Arctiinae species of Arequipa is presented. It is proposed that Amastus pallescens is a new synonym of Amastus cellularis. The female of A. cellularis is reported for the first time. The Magnoptera watsoni species was revalidated, which was synonimized a few years ago with Amastus walkeri. It was collected during 2017-2018, in 16 evaluation stations that included 4 altitudinal ranges: 0-1500, 1500-2500, 2500-3500, 3500-4500 m.